Soft power the means to success in world politics - Nye, Joseph S. (New York Public Affairs, 2004)
Joseph Nye coined the term "soft power" in the late 1980s. It is now used frequently?and often incorrectly?by political leaders, editorial writers, and academics around the world. So what is soft power? Soft power lies in the ability to attract and persuade. Whereas hard power?the ability to coerce?grows out of a country's military or economic might, soft power arises from the attractiveness of a country's culture, political ideals, and policies.
Includes bibliographical references and index.
Keywords: Power (Social sciences) --United States